Within sacred boundaries: the limitations of saintly justice in the province of Narbonne around the year 1000. Issue 3 (26th May 2020) - Matthews, Adam C.
ABSTRACT: Around the year 1000, judges from the ecclesiastical province of Narbonne (southern France and Catalonia) crafted judicial strategies that reinforced the region's Visigothic Code with the power of saints – conceived as gatekeepers to God's heavenly courtroom – to validate the oaths of witnesses. This practice merged liturgically grounded ideas about supernatural forces and space with a law code that prioritised secular authority. To forestall opposition to rulings, officials sometimes held proceedings in churches. This paper examines two unusual cases illustrating the challenges such strategies faced, given the perception that saints were not omnipresent. These disputes raise questions about the nature of saints, the degree of agency humans attributed to them and the utility of sacred spaces for legal ritual. In the province, saints were powerful, but constrained by their inability to act beyond the walls of consecrated sanctuaries housing their relics. This relegated saints to supplementary roles in law.